1994
DOI: 10.2307/2410359
|View full text |Cite
|
Sign up to set email alerts
|

High Inbreeding Depression, Selective Interference Among Loci, and the Threshold Selfing Rate for Purging Recessive Lethal Mutations

Abstract: The evolutionary dynamics of recessive or slightly dominant lethal mutations in partially self-fertilizing plants are analyzed using two models. In the identity-equilibrium model, lethals occur at a finite number of unlinked loci among which genotype frequencies are independent in mature plants. In the Kondrashov model, lethals occur at an infinite number of unlinked loci with identity disequilibrium produced by partial selfing.If the genomic mutation rate to (nearly) recessive lethal alleles is sufficiently h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
248
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(258 citation statements)
references
References 30 publications
9
248
1
Order By: Relevance
“…The difference is largest when deleterious alleles are substantially recessive (h < 0.2) and the mutation rate is high. This deviation is a consequence of 'selective interference' (Lande et al, 1994), wherein identity disequilibria among loci reduces the efficiency of selection. For low outcrossing rates (high selfing), the mutational load predicted by OC74 consistently overestimates the Q predicted by K85 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference is largest when deleterious alleles are substantially recessive (h < 0.2) and the mutation rate is high. This deviation is a consequence of 'selective interference' (Lande et al, 1994), wherein identity disequilibria among loci reduces the efficiency of selection. For low outcrossing rates (high selfing), the mutational load predicted by OC74 consistently overestimates the Q predicted by K85 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Consider selective interference, which is responsible for the large difference between single and multi-locus predictions in Figure 2. This effect is often associated with deleterious mutations of large effect because Lande et al (1994) focused on embryonic lethals in their study of interference. Their parameter sets were clearly motivated by empirical studies, but it is worth noting that selective interference is not a consequence of high selection coefficients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purging of recessive mutations is most effective when there is high variance in fitness among selfed zygotes. Lande et al (1994) have demonstrated that when load is high, viability of selfed zygotes is uniformly near zero, and thus there is little opportunity for purging. Essentially, with high load, selfed seeds are inviable, and embryo competition will have little effect on the frequency of recessive mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Fitness interactions are multiplicative across loci, and it is assumed throughout that mutations are sufficiently rare that mean fitness of selfs is greater than zero (see Lande et a!., 1994 …”
Section: Introductionmentioning
confidence: 99%